Leisure Constraints to Participation in Competitive Activities and Intramural Sports: Comparing International and Domestic Students - Cho, Dongwook; Price, Taryn (Journal of International Students, 2018)
The continuous increase in enrollment of international collegiate students into higher education highlights the importance of assessing diverse leisure opportunities that meet the needs of a diverse student population. The current study assessed the influence of leisure constraints on intramural and competitive sport participation rates between domestic and international students. A total of 273 participants were included for analysis (196 domestic students & 77 international students). International students were observed to have significantly higher intrapersonal and structural leisure constraints to participate in intramural sports, while domestic students had significantly lower leisure constraints. Implications of the study’s findings are discussed to include unique programming strategies for recreation and university administrators.